1977
DOI: 10.1161/01.cir.55.5.767
|View full text |Cite
|
Sign up to set email alerts
|

HDL cholesterol and other lipids in coronary heart disease. The cooperative lipoprotein phenotyping study.

Abstract: SUMMARYThe relation between coronary heart disease (CHD) prevalence and fasting lipid levels was assessed by a case-control study in five populations with a total of 6859 men and women of black, Japanese and white ancestry drawn from subjects aged 40 years and older from populations in Albany, Framingham, Evans County, Honolulu and San Francisco.In each major study group mean levels of high density lipoprotein (HDL) cholesterol were lower in persons with CHD than in those DURING THE PAST TWO DECADES considerab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

13
358
1
20

Year Published

1980
1980
2010
2010

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 1,412 publications
(392 citation statements)
references
References 24 publications
13
358
1
20
Order By: Relevance
“…All these (larger WC, increased TGs and FSG, along with lower HDL-C levels), in addition to being the components and the criteria for the diagnosis for the metabolic syndrome, 11 are also well-established markers for increased CVD risk. [3][4][5][6][7][8][9] The prevalence of two or more disordered cardiometabolic risk factors other than high BP was significantly higher in adults with PreHTN. The fact that subjects with hypertension significantly differ from those with desirable BP (normotension) in BMI, WC, FSG, hemoglobin A1c, total-C, LDL-C, whereas the subjects with PreHTN differ significantly from those with normotension in BMI, WC, FSG, hemoglobin A1c, Insulin, homeostasis model assessment, C-reactive protein, total-C, LDL-C, TG and cardiac risk ratios attests to PreHTN being strongly associated with an adverse cardiometabolic risk profile.…”
Section: Discussionmentioning
confidence: 98%
See 2 more Smart Citations
“…All these (larger WC, increased TGs and FSG, along with lower HDL-C levels), in addition to being the components and the criteria for the diagnosis for the metabolic syndrome, 11 are also well-established markers for increased CVD risk. [3][4][5][6][7][8][9] The prevalence of two or more disordered cardiometabolic risk factors other than high BP was significantly higher in adults with PreHTN. The fact that subjects with hypertension significantly differ from those with desirable BP (normotension) in BMI, WC, FSG, hemoglobin A1c, total-C, LDL-C, whereas the subjects with PreHTN differ significantly from those with normotension in BMI, WC, FSG, hemoglobin A1c, Insulin, homeostasis model assessment, C-reactive protein, total-C, LDL-C, TG and cardiac risk ratios attests to PreHTN being strongly associated with an adverse cardiometabolic risk profile.…”
Section: Discussionmentioning
confidence: 98%
“…[3][4][5] Higher levels of serum triglycerides (TGs) (4150 mg per 100 ml) and low levels of high-density lipoprotein-cholesterol (HDL-C) (o40 mg per 100 ml in men and o50 mg per 100 ml in women) have been similarly associated with elevated risk for vascular events. [6][7][8] Fasting serum glucose (FSG) levels over 100 mg per 100 ml increase the risk for developing cardiovascular disease (CVD). 9 Prediabetes (American Diabetes Association criteria: fasting blood glucose 100-125 mg per 100 ml and/or 2 h post-meal blood glucose 140-199 mg per 100 ml) is associated with abnormal circadian BP variability, 10 a plausible functional measure of the mechanism underlying increased adverse cardiovascular events.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Numerous studies examining the general population have documented the association of coronary heart disease with low HDL and HDL2 cholesterol levels [45,46]. Studies examining populations of diabetic subjects have also demonstrated the association of low HDL and HDL2 cholesterol levels with coronary heart disease [16,47,48].…”
Section: Discussionmentioning
confidence: 99%
“…This paper presents a relatively simple method for measuring serum HDL:LDL lipid ratios and evaluates the usefulness of this method as a predictive indicator for risk of CHD, which has been correlated positively with serum LDL-cholesterol levels (Miller and Miller, 1975;Rhoads et al, 1976) and negatively with HDL-cholesterol (Carlson and Ericsson, 1975;Castelli et al, 1977;Miller et al. 1976).…”
Section: Introductionmentioning
confidence: 99%